CULTURAL BELIEFS AND HEALTHCARE UTILIZATION IN ANAMBRA STATE, NIGERIA - T. Ugwu, Ugochukwu; O. Okpala, Chiemerie (African Journal of Social and Behavioural Sciences, 2024)
This study investigated cultural beliefs and healthcare utilization in Anambra State, Nigeria. The study used a mixed-methods research design. This type of research involves the collection and analysis of data via both quantitative and qualitative methods. The quantitative data were gathered via questionnaires, and the qualitative data were collected via an in-depth interview guide (IDI). The quantitative data collected were processed via SPSS (23) and analysed with descriptive statistics, whereas the data from the qualitative interviews were coded into themes that reflected the objectives of this study. Evidence suggests that cultural beliefs affect healthcare utilization. In addition to cultural beliefs, economic factors are other factors that prevent modern healthcare utilization. With the belief that traditional medicine is potent, it presents a viable alternative. The major factor is economic factors. The respondents believed that involving traditional healers in healthcare programs would help increase healthcare utilization. Additionally, reducing the cost of utilizing modern healthcare is a major intervention, among other findings. The results of this study suggest that further studies that are comprehensive enough to breed more data are needed to aid in generalization.